Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $n$ be a positive integer and $\mathbb{F}$ be a field. Suppose $A$ $\in$ $M_{n\times n}(\mathbb{F})$ and $P$ is and invertible matrix, such that $P \in M_{n\times n}(\mathbb{F})$. If $f$ is any polynomial over $\mathbb{F}$, prove that

$$f(P^{-1}AP) = P^{-1}f(A)P.$$

share|improve this question
Have you tried induction on the degree of $f$? –  ajotatxe Apr 20 at 0:11
No, I will think in the solution using induction. –  ViKaN Apr 20 at 0:36
No need for induction. Just write out an arbitrary polynomial and use algebraic properties. See the hint I gave below. –  Seth Apr 20 at 1:27

2 Answers 2

Hint: $(P^{-1}AP)^m = P^{-1}A^mP$.

share|improve this answer

I think I have the proof, let show you, I will be a little bit formal.

Let $f \in \mathbb{F}$[$X$]. Such that $f = \sum_{i=0}^{n}c_ix^i$. For $n,c_i\in \mathbb{F}$.

Let $\mathcal{A}$ be a linear algebra, and we define $f(\alpha) = \sum_{i=0}^{n}c_i\alpha^i$, for all $\alpha \in \mathcal{A}$.

First we will show that $(P^{-1}AP)^m = P^{-1}A^mP.$ This mean the following,

$(P^{-1}AP)^m$ = $(P^{-1}AP)\cdot(P^{-1}AP)\ldots(P^{-1}AP)$ m times.

But as the multiplication of matrices is associative, we get that following:

$(P^{-1}AP)^m = P^{-1}A(PP^{-1})A(PP^{-1})\ldots(PP^{-1})AP$ $= P^{-1}A^mP$ ----- ($\ast$).

So by the definition of our funtion we get:

$$f(P^{-1}AP) = \sum_{i=0}^{n}c_i(P^{-1}AP)^i$$ by ($\ast$) we can state the following: $$=\sum_{i=0}^{n}c_iP^{-1}A^iP$$ $$=P^{-1}(\sum_{i=0}^{n}c_iA^i)P$$ $$=P^{-1}f(A)P$$ As we wanted to proof. $\blacksquare$

share|improve this answer
Good job, this was what I had in mind. –  Seth Apr 20 at 1:38

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.